Riba dalam Perspektif Ekonomi Islam - Rahmani Timorita Yulianti (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2002)
In technical term, the usury is often defined as the taking of capital interest in wrong way. There are some ideas in describing of the usury, but commonly it is explained as taking the interest, whether in business transaction or in loaning wrongly and it is ought to be in contradiction with the Islamic principle of transaction. This concept of usury has been practicing since the Romeage, Greek, Jahiliiyah and even after coming of Islam, the taking of money interest is still done by people. Right now, the social ethics has been changed to social economic. The money interest is not only prohibited by Islam, but also by Jewish and Christianity. This prohibiting can be looked up in Holy Qur'an, Prophet Tradition, and other Holy Book of Jewish and Christian. The resistance of usury practice is so hard, for its negative effects to the society, moral spiritual, social life and economic field. In Islamic perspective, the usury is will make the unstable and broken of economic system, so it must be prohibited. The Islamic economy offers and suggests to the human being to do the real and productive effort through the infestation and leaving the usury.